2008
DOI: 10.1007/s10495-008-0212-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization of melanoma cells through combined inhibition of protein regulators of cell survival

Abstract: The incidence of melanoma continues to dramatically increase in most Western countries with predominantly Caucasian populations. However, only limited therapies for the metastatic stage of the disease are currently available. The main purpose of this study is to determine approaches that can substantially increase radiosensitivity of melanoma cells. The PI3K-AKT, NF-κB and COX-2 pathways, which are involved in the radioprotective response, are highly active in melanoma cells. Pharmacological suppression of COX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 37 publications
0
50
0
3
Order By: Relevance
“…26 Given the rising incidence of melanoma and the paucity of effective treatments, there is much hope for targeted therapies and promising agents, including those that act on apoptosisregulating molecules. 11,27 Herein, we showed a novel role for FKBP51 as a marker of melanocyte malignancy and involvement in the protection of melanoma against Rx-induced apoptosis. FKBP51 is a large immunophilin that exerts important biological functions in the cell, among which is the regulation of the steroid hormone response as a component of the steroid hormone receptor complex 28 and the control of NF-kB activation as a cofactor of the IKKa subunit in the IKK complex.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…26 Given the rising incidence of melanoma and the paucity of effective treatments, there is much hope for targeted therapies and promising agents, including those that act on apoptosisregulating molecules. 11,27 Herein, we showed a novel role for FKBP51 as a marker of melanocyte malignancy and involvement in the protection of melanoma against Rx-induced apoptosis. FKBP51 is a large immunophilin that exerts important biological functions in the cell, among which is the regulation of the steroid hormone response as a component of the steroid hormone receptor complex 28 and the control of NF-kB activation as a cofactor of the IKKa subunit in the IKK complex.…”
Section: Discussionmentioning
confidence: 93%
“…It is noted that NF-kB controls apoptosis at the genetic level and has been implicated in the radioresistance of melanoma. 11,12 It is widely known that the NF-kB transcription complex belongs to the Rel family, which comprises five mammalian Rel/NF-kB proteins: RelA (p65), c-Rel, RelB, NF-kB1 (p50/p105), and NF-kB2 (p52/100). 13 The activity of NF-kB is controlled by cytoplasmic shuttling to the nucleus in response to cell stimulation.…”
mentioning
confidence: 99%
“…Johnson et al reported that melanoma cells were radiosensitized through combined inhibition of protein regulators of cell survival, namely suppression of cFLIP and Bcl-xL expression (15).…”
Section: Discussionmentioning
confidence: 99%
“…Rheb-GTP then activates mTORC1, which phosphorylates other downstream targets such as S6 kinase and 4-EBP-1. Akt substrates include Bad, Caspase 9, IKKα, NOS, TSC2, PRAS40, p27, MDM2, and GSK3β (Johnson et al, 2008). Akt mediated phosphorylation of these proteins leads to their activation or inhibition.…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%